IDENTIFIKASI POLA KOMUNIKASI INTERPERSONAL KELUARGA DALAM MENUNJANG KESEHATAN MENTAL MAHASISWA RANTAU DI IAIN KERINCI - Yola Tri Juli; Hengki Yandri (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2026)
This study aims to identify interpersonal communication patterns within families and their role in supporting the mental health of out-of-school students at IAIN Kerinci. Out-of-school students often face various challenges, such as separation from family, academic pressure, and social and cultural adaptation, which have the potential to impact their psychological well-being. In this context, interpersonal communication between students and their families is a crucial factor that can provide emotional support, a sense of security, and psychological empowerment. This study used a qualitative approach with descriptive methods to explore the form, frequency, and quality of communication between out-of-school students and their families. The results show that open, empathetic, and supportive communication patterns contribute significantly to maintaining emotional stability and reducing stress and anxiety levels. Conversely, minimal, rigid, or unresponsive communication tends to worsen students’ mental health. Therefore, the continuity of effective interpersonal communication within families is a key element in supporting the mental health of out-of-school students, especially at IAIN Kerinci.